MIXED INCIDENCE OF GASTRO-INTESTINAL PARASITOSIS IN A SINGLE SMALL RUMINANTS FLOCK - A. Latchumikanthan; E. Tamileniyan; M. Veeraselvam; V. Arul; R. Velusamy (Indian Journal of Veterinary and Animal Sciences Research, 2026)
A small ruminant flock of 19 Non-descript Goat and 9 Ramnad White Sheep were investigated for the complaint of anorexia, voiding of diarrhoeic watery faeces and sudden death of two lambs on previous day of presentation. Faecal samples were collected from the flock and subjected for routine parasitological examination. Microscopic examination of the faecal samples revealed mild to severe infection of Eimeria spp., Amphistome, Haemonchus contortus, Moniezia expansa and Trichuris spp. Mixed infection with 4 parasitic stages was observed in 6 (21.42%) animals, mixed infection with 3 parasitic stages in 8 (28.57%) animals, mixed infection with 2 parasitic stages in 12 (42.85%) animals were found. Eimeria spp. oocysts in faecal samples were further confirmed after sporulation using 2.5% potassium dichromate solution. Haemonchus contortus larvae were identified from faecal samples by culture using the jar method. Morphometry of oocysts, parasite eggs and larvae were also carried. Incidence of single parasite species infection was not recorded in this flock.